2005
DOI: 10.1038/nrc1547
|View full text |Cite
|
Sign up to set email alerts
|

Bleomycins: towards better therapeutics

Abstract: Bleomycins are a family of glycopeptide antibiotics that have potent antitumour activity against a range of lymphomas, head and neck cancers and germ-cell tumours. The therapeutic efficacy of the bleomycins is limited by development of lung fibrosis. The cytotoxic and mutagenic effects of the bleomycins are thought to be related to their ability to mediate both single-stranded and double-stranded DNA damage, which requires the presence of specific cofactors (a transition metal, oxygen and a one-electron reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
511
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 573 publications
(534 citation statements)
references
References 94 publications
10
511
0
6
Order By: Relevance
“…This observation may suggest that the main toxic intermediates formed by bleomycin are those related to clustered DNA damage, including juxtaposed AP sites and/or 3 ¶ damagecontaining single-strand breaks, or complex DNA doublestrand breaks (48). Although APE1 has been shown to excise a synthetic mimic of a trapped 3 ¶-topoisomerase I protein (i.e., a 3 ¶-DNA tyrosyl residue; ref.…”
Section: Discussionmentioning
confidence: 93%
“…This observation may suggest that the main toxic intermediates formed by bleomycin are those related to clustered DNA damage, including juxtaposed AP sites and/or 3 ¶ damagecontaining single-strand breaks, or complex DNA doublestrand breaks (48). Although APE1 has been shown to excise a synthetic mimic of a trapped 3 ¶-topoisomerase I protein (i.e., a 3 ¶-DNA tyrosyl residue; ref.…”
Section: Discussionmentioning
confidence: 93%
“…23 When initiating pulmonary fibrosis with bleomycin, the most common administration route is intratracheal administration, which causes tissue necrosis, followed by an extensive inflammation and subsequent fibrosis. However, we have previously shown that repeated subcutaneous administration of a low-dose bleomycin results in a very different process, where fibrosis and inflammation develop in parallel resulting in increased proliferation rather than apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Bleomycin induces oxidative DNA damage and subsequent cell death after formation of a complex with iron (or copper) and oxygen, which generates free radicals able to create DNA single‐ and double‐strand breaks (Hecht 2000; Chen and Stubbe 2005). Notably, this drug is also able to oxidatively damage other cellular targets such as RNA, proteins, and lipids (Chen and Stubbe 2005). Bleomycin‐induced adverse effects include GI disorders, myelosuppression, cutaneous reactions, and pulmonary toxicity, in particular severe and life‐threatening lung fibrosis (Froudarakis et al.…”
Section: Introductionmentioning
confidence: 99%
“…2015). The pathophysiology of bleomycin lung toxicity seems complex, but could involve oxidative stress, inflammation, and overproduction of profibrotic cytokine transforming growth factor‐ β (TGF β ) (Chen and Stubbe 2005; Kikuchi et al. 2011; Froudarakis et al.…”
Section: Introductionmentioning
confidence: 99%